2010
DOI: 10.1073/pnas.1010198107
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoded dendritic marker sheds light on neuronal connectivity inDrosophila

Abstract: In recent years, Drosophila melanogaster has emerged as a powerful model for neuronal circuit development, pathology, and function. A major impediment to these studies has been the lack of a genetically encoded, specific, universal, and phenotypically neutral marker of the somatodendritic compartment. We have developed such a marker and show that it is effective and specific in all neuronal populations tested in the peripheral and central nervous system. The marker, which we name DenMark (Dendritic Marker), is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
227
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(251 citation statements)
references
References 58 publications
14
227
0
Order By: Relevance
“…Since EM studies of s-LNv axonal projections had revealed they have input synapses (Yasuyama and Meinertzhagen, 2010), we tested if s-LNv plasticity is also associated with altered accumulation of post-synaptic components. We used DenMark to mark dendrites (Nicolai et al, 2010) and found that DenMark levels at ZT14* are ~4-fold higher than at ZT2* (Figure 7C). Increasing Rho1 activity by inducing Rho1 CA increased the normally low DenMark levels at ZT2*, whereas reducing Pura levels using Pura shRNA reduced the high DenMark levels at ZT14*, although both manipulations left reduced amplitude DenMark oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…Since EM studies of s-LNv axonal projections had revealed they have input synapses (Yasuyama and Meinertzhagen, 2010), we tested if s-LNv plasticity is also associated with altered accumulation of post-synaptic components. We used DenMark to mark dendrites (Nicolai et al, 2010) and found that DenMark levels at ZT14* are ~4-fold higher than at ZT2* (Figure 7C). Increasing Rho1 activity by inducing Rho1 CA increased the normally low DenMark levels at ZT2*, whereas reducing Pura levels using Pura shRNA reduced the high DenMark levels at ZT14*, although both manipulations left reduced amplitude DenMark oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…NPF is required for the NPF activation-induced preference. Distribution of NPF neurons in the central brain (A) and ventral nerve cord (B) of the fly, as visualized by the expression of the cell polarity markers DenMark (dendrites) and Syt::GFP (synaptic terminals) (42,43) driven by the NPF-GAL4 driver. Positions of the large P1 and L1-l neurons, and the FSB are indicated.…”
Section: Significancementioning
confidence: 99%
“…MVP2 dendrites are situated to receive postsynaptic input from KC axons, perhaps mediating functional correlations among specific groups (Tanaka et al, 2008). Double labeling with antibodies against Fasciclin II (FasII) to mark KC axons (Gatto et al, 2014) and the specific dendrite reporter UAS-DenMark (DM) (Nicolai et al, 2010) shows MVP2 arbors occupy a large MB spur region (Fig. 1B).…”
Section: Two Classes Of Mushroom Body Extrinsic Input and Output Neuronsmentioning
confidence: 99%